2020
DOI: 10.1021/acs.langmuir.0c02482
|View full text |Cite
|
Sign up to set email alerts
|

Developing Scattering Morphology Resolved Total Internal Reflection Microscopy (SMR-TIRM) for Orientation Detection of Colloidal Ellipsoids

Abstract: Micrometer scale colloidal particles experiencing ∼kT scale interactions and suspended in a fluid are relevant to a broad spectrum of applications. Often, colloidal particles are anisotropic, either by design or by nature. Yet, there are few techniques by which ∼kT scale interactions of anisotropic particles can be measured. Herein, we present the initial development of scattering morphology resolved total internal reflection microscopy (SMR-TIRM). The hypothesis of this work is that the morphology of light sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…It should be noted that at t 3 , the sRBC was released from the boundary (LN surface) and the integrated TIR intensity during this phase dropped to approximately 0.5. This kind of intensity change is roughly consistent with the average distance between sRBC and the LN surface increasing on the order of ∼ O (10 nm) from the initial equilibrium distance, although a more precise measure of height change would require a deeper understanding of how scattering depends on the orientation and shape of the RBC (37,38). The sRBC displayed a dragging motion until t 4 and tumbled at t 5 .…”
Section: Single-cell Detachment Under Tirm: Dynamic Variation Of Adhe...supporting
confidence: 69%
See 2 more Smart Citations
“…It should be noted that at t 3 , the sRBC was released from the boundary (LN surface) and the integrated TIR intensity during this phase dropped to approximately 0.5. This kind of intensity change is roughly consistent with the average distance between sRBC and the LN surface increasing on the order of ∼ O (10 nm) from the initial equilibrium distance, although a more precise measure of height change would require a deeper understanding of how scattering depends on the orientation and shape of the RBC (37,38). The sRBC displayed a dragging motion until t 4 and tumbled at t 5 .…”
Section: Single-cell Detachment Under Tirm: Dynamic Variation Of Adhe...supporting
confidence: 69%
“…Our team is developing a new class of TIRM, named Scattering Morphology Resolved TIRM (SMR-TIRM), suitable for probing interactions between anisotropic particles and a neighboring surface. We recently described the implementation of SMR-TIRM on anisotropic particles (37, 38). This improvement expands the applicability of TIRM to biological targets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One challenge with the application of conventional TIRM, however, is utilizing this technique with novel anisotropic particles [17]. Particles with a non-spherical shape or anisotropic optical properties will cause light scattered from the particle to depend upon not only the separation distance, but also its orientation with respect to the evanescent wave [18,19]. Decoding the signature of this scattered light for a specific type of anisotropic particle is a current challenge that Scattering Morphology Resolved Total Internal Reflection Microscopy (SMR-TIRM) intends to address.…”
Section: Introductionmentioning
confidence: 99%
“…SMR-TIRM uses the morphology of scattering in addition to the integrated intensity. Recent experimental and simulation results have shown that both the morphology and integrated intensity sensitively depend upon the orientation of an ellipsoidal colloid [18]. Primarily, this information could be used to estimate the orientation and position of the ellipsoid, thereby providing the necessary information to assemble the potential energy landscape for an anisotropic particle [20].…”
Section: Introductionmentioning
confidence: 99%